Material educativo e a interculturalidade na formação Escola da Terra Capixaba - Lima, Kelly Cristina Soares (2021)
This study aimed to analyze the discourses in/about the educational materials of the Escola da Terra Capixaba Extension Course offered by the Federal University of Espírito Santo (Ufes), in an inter-institutional partnership (Foerste, 2005) with City Halls, Social Movements, the State Education Secretariat of Espírito Santo (Sedu), the National Union of Municipal Education Directors in ES (Undime / ES), the Secretariat for Continuing Education, Literacy, Diversity and Inclusion of the Ministry of Education (Secadi / MEC), with a first offer from September 2015 to November 2016. We sought to understand how the discourses acquired by the educational materials, made available in the Virtual Learning Environment (VLE) of the Escola da Terra Capixaba course, contribute to a continuing education of teachers who value intercultural dialogues. This study was bibliographical research, with a qualitative approach, which included a documental analysis and an analysis of three rounds of online conversation, carried out with the coordinators and some professors-researchers. The discussion sought to interface with the studies by Káplun (2003) on educational materials; Bakhtin (2011) and Volóshinov (2018) regarding discourse analysis; Fornet-Betancourt (2001) and Candau (2010; 2020) on interculturality and Freire (1887; 1989; 2002) on educational practice. We analyzed the educational materials available in the VLE, especially those from module II, entitled “Culture(s) Interculturality and Interdisciplinarity in Rural Education”; the projects posted by the course-teachers for one of the activities of the module and the material produced from the rounds of conversation. The results showed that the course promoted mechanisms of intercultural appreciation, enabled the production of materials with great potential for reverberation, and contributed to signaling the importance of interinstitutional partnerships in teacher education.